A STUDY ON THE PHYTOCHEMICAL AND ANTIMICROBIAL PROPERTIES OF METHANOL AND METHANOL/WATER EXTRACT OF AERIAL PART OF PHYLLANTHUS NIRURI (FUDMA JOURNAL OF SCIENCES, 2023)
This work focuses on the phytochemical and antimicrobial screening of the methanol and mixture of methanol/water extracts. The phytochemical screening of the methanol extract revealed the presence of Carbohydrate, Glycoside, Anthraquinones, Steroidal Triterpenes, Flavonoids, Tannins and Alkaloids while Cardiac glycoside and saponins were found to be absent. The Methanol/water mixture extract reveal the presence of Carbohydrate, Anthraquinones, Cardiac Glycoside, Saponins, Steroidal Triterpenes, Flavonoids, Tannins and Alkaloids with the absence of Anthraquinones. The antimicrobial activities of the extracts were carried out to ascertain which fraction of the extracts was more sensitive to the test organisms. The methanol extract was found to be sensitive with the following zone of inhibition to Staphylococcus aureus (19 mm), Streptococcus Pyrogenes (19 mm), Salmonella typhi (22 mm), Shigellia dysenteric (21 mm), Pseudomonas aeruginosa (20 mm) and Microsperum canis (15 mm) and resistant to Escherichia coli, Proteus Mirabilis and Trichophyton without zone of inhibition. While the methanol/water extract was found to be sensitive to Streptococcus Pyrogenes (21 mm), Escherichia coli (20 mm), Shigellia dysenteric (20 mm), Pseudomonas aeruginosa (19 mm), and Trichophyton (17 mm) while Staphylococcus aureus, Salmonella Typhi, Proteus mirabilis and Microsperum canis were resistant to the methanol/water extract without zone of inhibition. Based on the activities of these extracts on the selected microbes their Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration/Minimum Fungicidal Concentration (MBC/MFC) were carried out to ascertain their level of activities
Keywords: Inhibition, Organisms, Resistance, Maceration, Flavonoid, Salmonella Typhi